2007
DOI: 10.1002/elps.200600348
|View full text |Cite
|
Sign up to set email alerts
|

Full‐fledged proteomic analysis of bioactive wheat amylase inhibitors by a 3‐D analytical technique: Identification of new heterodimeric aggregation states

Abstract: Full-fledged proteomic analysis of bioactive wheat amylase inhibitors by a 3-D analytical technique: Identification of new heterodimeric aggregation statesWheat proteinaceous a-amylase inhibitors (a-AIs) are increasingly investigated for their agronomical role as natural defence molecules of plants against the attack of insects and pests, but also for their effects on human health. The wheat genomes code for several bioactive a-AIs that share sequence homology, but differ in their specificity against a-amylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…To evaluate the presence of aAI that are not recognized by PABs but that still exert an inhibition activity towards amylases, a reverse zymographic technique was applied (Zoccatelli et al, 2007). The accessions were challenged with human salivary amylase and with a pest amylase and showed that T.b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate the presence of aAI that are not recognized by PABs but that still exert an inhibition activity towards amylases, a reverse zymographic technique was applied (Zoccatelli et al, 2007). The accessions were challenged with human salivary amylase and with a pest amylase and showed that T.b.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the potential aAIs present in AA accessions were analyzed by means of a recent technique called anti-zymogram, or reverse zymogram (Zoccatelli et al, 2007). U-PAGE has been selected as separation technique since although the quaternary structure of aAIs is denatured, the tertiary structure is reversibly affected by urea, leading to the restoration of the inhibition activ- ity.…”
Section: Reverse Zymography Reveals That Einkorn Aais Posses Differenmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency against the amylases from a particular source is correlated with the inhibitor aggregation state and structural features of protein sequences [4]. Based on the degree of polypeptides aggregation, monomeric, homodimeric and heterotetrameric forms have been identified in wheat flour [9]. Due to the related structures of these proteins, efficient separation techniques are crucial to elucidate their nature.…”
Section: Introductionmentioning
confidence: 99%